2020
DOI: 10.5847/wjem.j.1920-8642.2020.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Headache may not be linked with severity of coronavirus disease 2019 (COVID-19)

Abstract: Coronavirus disease 2019 (COVID-19) is a highly infectious disease. By March 10, 2020, COVID-19 was in over 109 countries having infected over 113,702 people. [1] As the number of deaths keeps rising and with no vaccine, many countries are experiencing one of the most challenging times in their history. We conducted a meta-analysis to understand the role of headache as a clinical presentation with the severity of COVID-19. Articles published in English and Chinese were searched on PubMed. Each result was caref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
(7 reference statements)
0
8
0
1
Order By: Relevance
“…Die Schwere der COVID-19-Infektion scheint zwar nicht in Zusammenhang mit dem Vorhandensein oder Nicht-Vorhandensein der Kopfschmerzen zu stehen [27]. Es gibt aber Hinweise darauf, dass Kopfschmerzen mit einem kürzeren Verlauf der Infektionserkrankung verbunden sein könnten [20].…”
Section: Kopfschmerzen Als Symptom Einer Covid-19-infektionunclassified
“…Die Schwere der COVID-19-Infektion scheint zwar nicht in Zusammenhang mit dem Vorhandensein oder Nicht-Vorhandensein der Kopfschmerzen zu stehen [27]. Es gibt aber Hinweise darauf, dass Kopfschmerzen mit einem kürzeren Verlauf der Infektionserkrankung verbunden sein könnten [20].…”
Section: Kopfschmerzen Als Symptom Einer Covid-19-infektionunclassified
“…Almost a year later, it has infected about 85,892,625 people causing 1,857,399 deaths worldwide [1,3,4]. Since many countries have limited health care resources and intensive care units [3], many researchers studied early data to find possible risk factors that can lead to a more severe outcome of this virus [1,[5][6][7][8][9][10][11][12][13]. Analysis of SARS-COV-2 showed that the virus engages the angiotensin-converting enzyme 2 (ACE2) as a receptor to penetrate human cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we comprehensively analyzed the clinical characteristics and laboratory fi ndings, and screened out six diff erentiating factors for COVID-19: age >34 years, temperature ≤37.5 ℃, no sputum or myalgia, lymphocyte ratio ≥20% and CK-MB >9. patient with a score >18 was very likely to diagnose COVID-19. At present, viral nucleic acid detection may still be the most eff ective method to distinguish between different pathogen infections; [26,27] however, there is a certain false negative in nucleic acid detection, and there is a shortage of detection reagents in the outbreak of infectious disease. Although COVID-19 shares many similarities with H1N1, it has its own characteristics.…”
Section: Discussionmentioning
confidence: 99%